1997
DOI: 10.1103/physrevb.56.5128
|View full text |Cite
|
Sign up to set email alerts
|

Sequential vortex states upon lattice melting in untwinned single-crystalYBa2Cu3O

Abstract: Simultaneous measurements of the ac susceptibility and the dc magnetization of an untwinned single-crystal YBa 2 Cu 3 O 7 have been carried out to clarify the nature of vortex lattice melting. The first-order melting transition appears as a jump in the dc magnetization. Evidence for effectual pinning at temperatures above the melting transition is obtained as a sharp transition in Ј and a sharp peak in Љ of width 0.2 K in 10 kG. In addition, a precursor lattice softening phenomenon can be seen in Ј and Љ at te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
20
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 16 publications
(14 reference statements)
8
20
0
Order By: Relevance
“…Thermodynamic signatures of the underlying (discontinuous) melting transition in the pure system should thus be strongest across this boundary; this is consistent with magnetization experiments on untwinned and twinned single crystals of YBCO [6,38,[48][49][50]. However, the two stage nature of the transition implies that some part of the difference in density between ordered and liquid phases can be accomodated across the width of the sliver regime [52].…”
Section: Discussionsupporting
confidence: 48%
“…Thermodynamic signatures of the underlying (discontinuous) melting transition in the pure system should thus be strongest across this boundary; this is consistent with magnetization experiments on untwinned and twinned single crystals of YBCO [6,38,[48][49][50]. However, the two stage nature of the transition implies that some part of the difference in density between ordered and liquid phases can be accomodated across the width of the sliver regime [52].…”
Section: Discussionsupporting
confidence: 48%
“…Since H*(T) above T cp decreases along H m (T) and disappears, the second peak effect just below H m (T) is closely related to the enhanced vortex pinning due to the vortex lattice softening prior to the vortex lattice melting as reported previously. [39][40][41] These results indicate that H*(H) merges with both H m (T) and the premelting peak effect at the critical point for irradiated YBa 2 Cu 3 O y . The region between H*(T) and H m (T) above T cp is very narrow in the present study, so the result above mentioned is completely different from the recently reported second peak 29,42 which intersects H m (T) well below H cp for optimally doped and slightly underdoped YBa 2 Cu 3 O y .…”
mentioning
confidence: 78%
“…19,28,29 We would like to mention that a similar "premelting peak" very close to or even coincidental with thermally induced vortex melting has also been reported in YBa 2 Cu 3 O x at fields below the fishtail effect. 30,31 The relaxation behavior of induced critical currents in the region of this premelting peak shows many features, which are known from highly "fragile" 32 structural glass transitions in undercooled liquids. 31 This all suggests that the presently observed magnetization peak effect in Nb 3 Sn ͑and probably also in many other type-II superconductors͒ follows the same phenomenology, as found in supercooled structural liquids despite the fact that the vortex system is not supercooled in the traditional sense.…”
Section: Discussionmentioning
confidence: 99%